Physical activity and sport participation in veterans with extremity musculoskeletal disorders - Elahe Faraji; Ayoub Dabiri; Mostafa Allami; Mostajad Hosseini; Amir Hossein Barati (European Federation of Adapted Physical Activity, 2023)
Increasing the physical activity and sport participation rates of people with disabilities has been one of the most important targets of sport policy both at national and international levels. The purpose of the current investigation was to assess participation in sports or physical activities among Iranian veterans with extremity musculoskeletal disorders. Data were obtained from health needs assessment studies conducted among Iranian veterans with musculoskeletal disorders in a 12-year period between 2005 and 2017. The collected Information on sport or physical activity participation was analyzed using χ2 test, independent t-test, partial correlation coefficient and binary logistic regression (p < 0.05). Studies on 2644 veterans with extremity musculoskeletal disorders indicated that 37.6% (n = 994) of them participated in at least one type of sport or physical activity. The highest percentage of sport participation was 65% in bilateral upper limb amputees. Results from logistic regression analysis indicated that the chance of sport participation decreased with ageing while it increased with "Disability Percentage" assigned by the medical commission of the Veterans and Martyrs Affairs Foundation which is responsible for determining the disability rate of the veterans in Iran. It was observed that veterans with a higher "Disability Percentage" had a higher duration and frequency of sport or physical activity participation. The most popular sports among the subjects were track and field (20.1%, n = 192) and swimming (15.6%, n = 149). Generally, more than a third of the subjects participated in sports or physical activities in total and sport or physical activity participation was greater in the high-level lower extremity amputation group.